Timing characteristics of pulling force and ground force during Kuzushi and Tsukuri phases of Seio-nage - Imamura, R.; Parker, D. L.; Iteya, M. (Association for the Scientific Studies on Judo, Kodokan, 2015)
The purpose of this study was to continue investigations into the defi nition of throwing phases presented years ago by Jigoro Kano. The study also seeks to identify possible biomechanical markers that precede an ideal throw by combining concepts of body movement (kinematics) and body force generation from the ground (kinetics). Specifically, the study serves as a preliminary investigation to the relationship between tori`s pulling force and ground force during the kuzushi/tsukuri (KT) phase of the throw seio-nage.